A novel recycling system for nano-magnetic molecular imprinting immobilised cellulases: Synergistic recovery of anthocyanin from fruit and vegetable waste. (December 2016) - Yuan, Bo; Yang, Xù-qin; Xue, Ling-wei; Feng, Yan-nan; Jiang, Ji-hong
Highlights: Molecular imprinting magnetic nanoparticles have been developed to immobilise the cellulases. It has good reusability and stability in bio-catalytic processes. The immobilised amylase was enhanced than the free enzyme. Novel material could effective treat with FVW and recycle the anthocyanin from it. Abstract: Fruit and vegetable waste (FVW) is become a serious problem in developing countries. Enzymolysis is a potentially useful method for the treatment of FVW. In the present study, novel recycled magnetic molecular imprinting immobilised cellulases were prepared based on magnetic modified chitosan (MCTS) and Fe3 O4 . The properties of obtained were characterised by IR and grain-size measurements. Evaluation of a single factor affecting the loading efficiency of supports and the mixed immobilised enzymes showed better capacity than single immobilised, or free, enzymes. The immobilisation process could improve cellulase stability and repeatability of the method. Meanwhile, the kinetic parameters were also verified. The immobilised enzymes retained most of their capacity after 60 days' storage while free enzymes lost it within 30 days. Tests showed that the immobilised enzymes developed excellent capacity and five anthocyanins were collected.